2017
DOI: 10.21614/chirurgia.112.4.477
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B Cell Lymphoma in a Male Breast - A Rare Case Report

Abstract: RezumatLimfomul difuz cu celulă mare B mamar la bărbaţi reprezintă o entitate rară ce poate mima carcinomul mamar ca prezentare clinică, de aceea tratamentul iniţial pentru majoritatea pacienţilor rămâne cel chirurgical. Diagnosticul şi tratamentul precoce complementar, chimioterapia şi radioterapia, sunt foarte importante. Vom prezenta cazul unui bărbat de 56 ani diagnosticat cu limfom difuz cu celulă mare B, primitiv cu localizare mamară -formaţiune tumorală mamară fără limfadenopatie axilară. În urma biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…In the few reported male cases, like in the patient presented here, breast lymphoma mainly affected men in the middle-to-old age groups [2][3][4][5][6][7][8]. Being initially considered as Burkitt lymphoma, we here rendered the diagnosis of a so-called "high-grade B-cell lymphoma with MYC and BCL2 rearrangements" also called "double-hit lymphoma" with Burkitt morphology.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the few reported male cases, like in the patient presented here, breast lymphoma mainly affected men in the middle-to-old age groups [2][3][4][5][6][7][8]. Being initially considered as Burkitt lymphoma, we here rendered the diagnosis of a so-called "high-grade B-cell lymphoma with MYC and BCL2 rearrangements" also called "double-hit lymphoma" with Burkitt morphology.…”
Section: Discussionmentioning
confidence: 75%
“…To date, less than 50 cases of male breast lymphoma have been reported in the literature [1,2]. Clinical presentation of breast lymphoma in men usually resembles the more common carcinomas with a mammographically solitary well-circumscribed painless mass in the breast and/or the ipsilateral axillary lymph nodes commonly unilateral [3][4][5][6][7][8]. Previous reports on male breast lymphomas focused mainly on the clinical and pathological features of the tumor [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Wiseman and Liao confirmed the definition of PBL in 1972, including the following criteria: (1) sufficient tumor tissue for histological examination; (2) no previous lymphoid malignancy at regions outside the breast; (3) lymphoma primarily presented within breast regions; and (4) close associations between lymphoma and breast tissue (5). This infrequent tumor was found especially in females, and quite uniquely, there were a few case reports in males in previous literature studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Due to the extreme rarity and unspecific manifestations, male patients with PBL are easily misdiagnosed clinically, thus delaying the optimal treatment time window and causing great pain to patients during the period of seeking medical advice.…”
Section: Introductionmentioning
confidence: 80%
“…The standard treatment for male PBL remains unclear, and most of the reported cases were referred to the management for female patients ( 6 8 , 10 20 , 22 , 23 , 26 ). Our results demonstrated that chemotherapy and surgery did not significantly improve the survival outcome of male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in the present review, all eight male patients who received radiotherapy combined with other treatment modality were alive without evidence of disease after a median of 17 months [10,[24][25][26][27][28]. Four patients received higher than 30 Gy (they mostly received 50 Gy), and information about radiation dosage was not available in one patient [24].…”
Section: Treatmentmentioning
confidence: 96%